IMPLEMENTASI MODERASI BERAGAMA DALAM PEMBELAJARAN MATA KULIAH PENDIDIKAN KEALWASHLIYAHAN DI UNIVERSITAS MUSLIM NUSANTARA AL-WASHLIYAH MEDAN - Haidir Haidir; Muhammad Hizbullah; Yeltriana Yeltriana; Ismed Batubara (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
This research aims to explore the implementation of religious moderation in learning Kealwashliyahan Education at UMN Al-Washliyah. Religious moderation is an effort to promote balanced and tolerant attitudes and behaviors in terms of religion, which is very relevant in the context of Higher Education. This research was conducted using a qualitative approach with a descriptive method. Data were collected through interviews, observations, and documentation from lecturers and students involved in the course. The results showed that the implementation of religious moderation in learning Kealwashliyahan courses at UMN Al-Washliyah was carried out through 3 (three) things, namely a) Lecture planning which is reflected in the RPS of the Kealwashliyahan Education course, b) Lecture implementation which is reflected in 7 lecture materials and learning methods, namely discussion methods and case studies to encourage critical thinking and interfaith dialogue, and c) Lecture evaluation to emphasize the understanding and application of religious moderation in order to be able to be tolerant and inclusive in diversity among students.